IMPROVING LABOR RELATIONS AND HUMAN CAPITAL IN THE CONTEXT OF DEVELOPING THE DIGITAL ECONOMY (The Role of Exact Sciences in the Era of Modern Development, 2024)
This paper examines the impact of digital transformation on labor relations and human capital development in Uzbekistan. The rapid growth of the digital economy requires a rethinking of human capital as a critical factor in economic growth, particularly in the context of artificial intelligence and technological advancements. This study reviews the current trends and challenges in labor relations and explores strategies for enhancing human capital through modern technologies. A particular focus is placed on the integration of artificial intelligence with traditional management systems to optimize labor efficiency and innovation. The findings highlight the importance of digital literacy, organizational transformation, and effective leadership in accelerating human capital development, especially in emerging economies like Uzbekistan. Recommendations are made for policymakers and businesses on leveraging digital tools to improve human capital and foster sustainable economic development.